Assessment of practices and barriers toward nasogastric tube rehydration for moderate and severe dehydration due to diarrheal disease in under-five children among health centers in Gamo Zone, Ethiopia - Tsegazeab Ayele; Muluken Birhanu; Solomon Kassa; Sayih Mehari Degualem; Habtamu Wondmagegn; Kidus Temesgen; Habtamu Esubalew Bezie; Tamirayehu Abayneh; Maycas Gembe; Biniyam Demisse Andarge (PLoS ONE, 2026)
Introduction Dehydration from diarrheal diseases remains a common cause of morbidity and mortality in developing countries. Nasogastric tube is an easy, efficient, and cost-effective method of management that could be a key to minimizing deaths from diarrheal disease. As such, this study assessed the current practices and barriers toward using nasogastric tube for managing moderate to severe dehydration in under-five children. Purpose To assess the practices and barriers toward the management of moderate to severe dehydration using nasogastric tube in under-five children among health centers in Gamo Zone, South Ethiopia. Methods A qualitative study design was conducted among healthcare professionals at selected health centers in Gamo Zone. Data about the practice pattern of managing moderate to severe dehydration and barriers toward nasogastric tube utilization were obtained via in-depth interview. Data were reviewed using constant comparative analysis to identify emerging themes, and axial coding was performed to make connections between categories to organize themes into causal relationships. Hypotheses and concepts were developed inductively from the data. Results In our study, of thirty participants, 21 (70.0%) correctly diagnosed severe dehydration, while 9 (30.0%) diagnosed moderate dehydration. Among those who diagnosed severe dehydration, 5 (23.8%) recommended intravenous resuscitation, and 16 (76.2%) chose oral rehydration. After being informed of failed attempts, four chose to refer, and one clinician remained fixed on intravenous resuscitation, while the remaining 16 clinicians opted for nasogastric tube. Major challenges mentioned by the participants in managing dehydration were late presentation of the patients and equipment shortage. Conclusion Participants in our study were aware of the significance of nasogastric tube for the treatment of moderate to severe dehydration. However, a gap in clinical skills, a lack of continuous training, high clinician turnover, and institutional policies limiting nasogastric tube utilization for the management of dehydration were major challenges. Therefore, improving clinicians’ skills through continuous training and improving management protocol is essential in ensuring safe and effective rehydration and better patient outcomes.